Central African Economic and Monetary Community (CEMAC) : Staff Report on Common Policies of Member Countries. (IMF Staff Country Reports; Country Report, 2014)
Regional growth weakened in 2013 due to a fall in oil production in most countries. GDP growth is expected to pick-up in 2014 due to the recovery of oil production and the continuation of the implementation of public investment plans in most of CEMAC countries. Despite large spending of oil wealth during the last years, poverty, income inequality and unemployment remain high. The business climate is one of the most challenging in Africa. The region's most pressing challenge is to implement structural reforms to promote sustainable and inclusive growth while adopting macro policies to preserve financial stability, ensure an efficient use of oil revenues and increase resilience to shocks.